2005
DOI: 10.1111/j.1365-3059.2005.01158.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of formulation on the rhizosphere competence and biocontrol ability of Trichoderma atroviride C52

Abstract: The rhizosphere competence of the biological control agent Trichoderma atroviride isolate C52 was studied on onion roots both in the glasshouse and in the field when introduced into soil in a range of formulations. Proliferation of T. atroviride in the rhizosphere was formulation-dependent. A pellet formulation maintained the fungal concentration at 10 5 cfu per g soil, whereas solid-substrate and seed-coating formulations gave concentrations of 10 4 and 10 1 cfu per g soil, respectively.To facilitate rhizosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(42 citation statements)
references
References 21 publications
3
33
0
4
Order By: Relevance
“…This result matches with the research finding by McLean et al, (2005). The isolates of Trichoderma atroviride showed excellent antagonistic activity against the fungal plant pathogens Aspergillus flavus and Fusarium solani causing rot diseases in various crops.…”
Section: Antagonistic Potential Of Trichoderma Atroviride Isolates Ussupporting
confidence: 81%
“…This result matches with the research finding by McLean et al, (2005). The isolates of Trichoderma atroviride showed excellent antagonistic activity against the fungal plant pathogens Aspergillus flavus and Fusarium solani causing rot diseases in various crops.…”
Section: Antagonistic Potential Of Trichoderma Atroviride Isolates Ussupporting
confidence: 81%
“…This study can be supported by findings of other workers reporting the role of Trichoderma as growth promoter. Several studies have documented that Trichoderma harzianum sensu lato, T. asperellum and T. asperelloides are highly rhizosphere competent and are able to stimulate growth and immune defense of plants (Harman et al, 2004). Mc Lean et al (2005 reported colonization and proliferation of Trichoderma atroviride (C52) when applied as bioformulation in onions against Sclerotium cepivorum providing nutrient to the biocontrol agent as compared to a very low colony count when applied only on seed.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, even though the E. rhinocerotis extract showed synergistic effects in the in vivo study, it did not produce a similar effect in the in vitro study. This could be a result of the type of biological formulation used, which could have affected the efficacy of the extract in the in vitro study [39,40].…”
Section: Discussionmentioning
confidence: 99%